A DFT Model study of the carbocations formed via the fjord- and bay-region diol epoxide metabolites of isomeric dibenzopyrenes and naphthopyrene - Borosky, Gabriela Leonor (2009)
A density-functional theory (DFT) study aimed at understanding structure-reactivity relationships in the oxidized metabolites of isomeric dibenzopyrenes (DBPs) and naphthopyrene (NP) is reported, These large polycyclic aromatic hydrocarbons (PAHs) contain a pyrene moiety and two benzannelated rings or a naphtho ring, and depending on the annelation mode, possess a fjord region (DB[a,i]P and N[1,2-Ci]P) or two or three bay-regions (DB[a, h]P, DB[a,i]P, and DB[a,e]P). Relative energies of the resulting carbocations were examined and compared, taking into account the available biological activity data on these compounds. Geometrical, electronic and conformational issues were considered. Charge-delocalization modes in the resulting carbocations were deduced, by the changes in charges derived from, natural population analysis (NPA). The reported biological activity of these toxic PAHs was found, to correlate with the degree of deviation from planarity of the aromatic system, in accord with the higher bioactivity of the fjord- and methylated bay-region compounds. On the other hand, relative formation of the possible carbocations derived from, each PAH, as well as the activity order for compounds presenting similar distortions, were explained by their relative carbocation stabilities. The covalent adducts formed via the fjord-region diol epoxide of DB[a,I]P and the exocyclic amino group and the N-7 of guanine were computed, and relative energies and geometries of the resulting adducts were examined. Furthermore, PAH-purine base adduct formation was modeled inside a DNA fragment by means of the ONIOM method.